Revisi Keyakinan atas Sinyal Informasi Akuntansi - MF. Arrozi Adhikara (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2010)
The purpose of this study was to determine the behavior of securities analysts’ beliefs revision in the valuation of shares which is determined by the sinyal quality of accounting information, unsystematic risk perception, and market risk as a measure of environmental uncertainty.This study uses explanatory-causal approach. Type of data is primary data and the collection method is a survey. The dimension of time used is one shot study. The respondents were securities analysts and the unit of analysis is the individual. Data analysis used Structural Equation Modeling (SEM) with AMOS.This study shows that the usefulness of accounting information has a positive influence on the beliefs revision and perceptions of risk and subjectivity of the return. Meanwhile, perception of risk has a negative influence on the subjectivity of the return. Furthermore, environment uncertainty has no influence on beliefs revision and subjectivity of the return. In addition, beliefs revision has a positive influence on subjectivity of return.Study findings indicate that signal quality of accounting information has information content; securities analysts have high confidence, prudent, disjunction attitude, volitional, sophisticated, rational behavior, and preferences of risk averter.Keywords: usefulness of accounting information, beliefs revision, perceptions of risk, environment uncertainty, subjectivity of return.